Assessment of the effects of cadmium and lead on pH and cation exchange capacity of soil under different plant canopy in the tropical wet-and dry climate - AO Eruola; NI Azike; IO Ogunyemi (Journal of Applied Sciences and Environmental Management, 2016)
The effects of heavy metals pollution on agricultural produce can not be over emphasize. To estimate the effect of heavy metal on pH and Cation Exchange Capacities of soil on incubation, relationships between availability of metals in soil after contamination were investigated for a range of soils and metals. Three concentrations (0 mg/kg, 2 mg/kg and 5 mg/kg) of lead and cadmium were added as nitrate solution as single and combine treatments to six soil samples under different plant canopy. The soils-metal were incubated at field capacity for 8 weeks under 250C. The exchangeable bases in soils were determined in IM ammonium acetate (pH 7.0) extract by FAAS and pH by pH meter with a combination electrode. The treatment is arranged in randomised complete design each in triplicates. The pH decreased from 7.02 to 6.70 and 6.63. Cation Exchange Capacities decreased from range of of 6.62 to range of 4.71 and 3.10 C mol kg-1 under single and combined treatments respectively for the six locations. These results enable us to understand natural attenuation of metal contamination and also to assess the risk of soil contamination by determining effects of metals reactions with CEC and pH in 8-weeks incubated soils after artificial contamination.